Exploring green banking performance of Islamic banks vs conventional banks in Bangladesh based on Maqasid Shariah framework - Julia, Taslima; Kassim, Salina (Emerald Group Publishing Ltd., 2019)
Purpose – Environmentaldegradationhasbeenidentiﬁedasoneofthemajorimpedimentsfordevelopment in Bangladesh. The World Health Organization has ranked Bangladesh fourth among the most polluted countries in the world. Faced with this challenge, the Government of Bangladesh introduced the Green Financing Policy and encouraged banks to participate in offering green ﬁnancing as part of the efforts to promote environment-friendly economic activities for sustainable economic development. This study aims to examine the ﬁnancial performance of selected commercial banks that offered green ﬁnancing in Bangladesh in the period from 2012 to 2014. Design/methodology/approach – In achieving this objective, the paper has divided the various sections of green banking policy under Maqasid Shariah framework of Imam Al-Ghazali, which is preserving faith, life, intellect, posterity and wealth. After that, green performance is compared between ﬁve conventional banks and ﬁve Islamic banks, according to the secondary data gathered from the annual reports and sustainability reports, as well as veriﬁed based on interviews. Finally, based on quantitative and qualitative thematic analysis approach, it is identiﬁed which banks meet most of the Shariah objectives along with performingsustainably. Findings – The study ﬁnds that none of the banks fully meet the green/sustainable policy requirements; however,the Islamic banks are ahead in preserving faith, intellect and wealth circulation. Research limitations/implications – This research is mostly based on secondary data; banks’ nondisclosure of green data was an impediment to run in-depth and fair comparisons. However, to check the reliability and validity of secondary data, two heads of sustainable banking department from conventional bank and two from Islamic bank have been interviewed. Practical implications – Based on the ﬁndings, several recommendations are made on ways to expedite green ﬁnancing,whichcanultimatelyenhancecontributionofIslamicbankstowardthesustainableeconomic growth of the country while fulﬁlling Maqasid Shariah. Social implications – Because the green banking policy aim is very much in line with Maqasid Shariah which is the aim of Islamic banks, Islamic banks can presumably contribute more to the sustainable economic growth of the country by aligning their entire operations with green policies. Originality/value – To the best of the authors’ knowledge, this study is perhaps the earliest initiative to compare Islamic and conventional banks’ green performances in Bangladesh.